2012
DOI: 10.1021/nl300173j
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenated TiO2 Nanotube Arrays for Supercapacitors

Abstract: We report a new and general strategy for improving the capacitive properties of TiO(2) materials for supercapacitors, involving the synthesis of hydrogenated TiO(2) nanotube arrays (NTAs). The hydrogenated TiO(2) (denoted as H-TiO(2)) were obtained by calcination of anodized TiO(2) NTAs in hydrogen atmosphere in a range of temperatures between 300 to 600 °C. The H-TiO(2) NTAs prepared at 400 °C yields the largest specific capacitance of 3.24 mF cm(-2) at a scan rate of 100 mV s(-1), which is 40 times higher th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

38
869
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,264 publications
(927 citation statements)
references
References 55 publications
38
869
2
5
Order By: Relevance
“…[12][13][14][15][16]) -such material was reported to cause a similar effect on the Pt-co-catalyzed photocatalytic H 2 -production or when used in a range of other electrochemical applications [17][18][19].…”
mentioning
confidence: 93%
“…[12][13][14][15][16]) -such material was reported to cause a similar effect on the Pt-co-catalyzed photocatalytic H 2 -production or when used in a range of other electrochemical applications [17][18][19].…”
mentioning
confidence: 93%
“…However, as an electrode material for SCs, TiO 2 suffers from relatively low electrical conductivity and poor electrochemical activity [101]. Recent reports demonstrated that introducing defects in TiO 2 can address these limits and thus improve specific capacitance and stability of TiO 2 materials [102,103]. The detailed microstructural investigation is critical to understand how the defect structure influences the electrical conductivity and electrochemical activity of TiO 2 .…”
Section: Defects In Tiomentioning
confidence: 99%
“…The aberration-corrected high-resolution TEM image revealed hillocks, terraces and surface corrugations as well as lattice bending, which offer openings to Li diffusion channels and thus facilitating the reversible Li incorporation. Chen et al [105] presented HRTEM analysis of the surface M A N U S C R I P T A C C E P T E D Another example of characterizing hydrogenated TiO 2 was presented by Lu [102].…”
Section: Defects In Tiomentioning
confidence: 99%
See 1 more Smart Citation
“…3c) shows a larger difference between the nitrided sample and the doped or native material. The nitrided electrode exhibits the obvious featureless shape of a double layer capacitor with a specific capacitance of 100 F g À1 at 100 mV s À1 -indicating a fast and high capacitance response for these nanostructured conductive electrodes (in fact, the current is higher than that reported under identical conditions for the best tube modification 36 ). This suggests that while the semiconductive materials capacitance values are partially dominated by their space charge layers, for the nitrided sample a metallic behavior (dominated by the Helmholtz layer) is observed.…”
mentioning
confidence: 91%